Analysis of Working Capital Management and Financial Ratios on Profitability of Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) in 2017-2021 - Ismail Mansyur (Jurnal Multidisiplin Madani, 2022)
This study aims to determine the effect of working capital, liquidity ratios, activity and solvency on profitability in manufacturing companies listed on the Indonesia Stock Exchange. This type of research is quantitative research using secondary data analysis in the form of financial statements of companies listed on the Indonesian stock exchange for the 2017-2021 period. Determination of the sample in this study using purposive sampling method. The data analyst used classical assumption test and multiple linear analysis. The independent variables used in this study are working capital (X1), liquidity (X2) activity (X3), and solvency (X4), while the dependent variable is profitability (Y). The results of the study show that: (1) There is no positive and significant effect on Working Capital on Profitability in Manufacturing Companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This is evidenced by the tcount value of 1.248 which is smaller than the ttable of 1.997, so Ha is rejected and Ho is accepted. (2) There is no positive and significant effect on Liquidity on Profitability in Manufacturing Companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This is evidenced by the tcount value of 0.555 which is smaller than the ttable of 1.997, so Ha is rejected and Ho is accepted. (3) There is a positive and significant influence on Activity on Profitability in Manufacturing Companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This is evidenced by the tcount value of 6.985 which is greater than the ttable of 1.997, so Ha is accepted and Ho is rejected. (4) There is a negative and significant influence on Solvability on Profitability in Manufacturing Companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This is evidenced by the tcount -2.291 greater than ttable -1.997 then Ha is accepted and Ho is rejected.